The development of liposomal medicine technology in a form of solution for injection - G. I. Borshchevskіy (Zaporozhye State Medical University, 2015)
Due to a number of important pharmacological effects, essential phospholipids today are widely used in medical practice. Aim. In order to develop technology of liposomal for injections «Lesfal» a number of technological tasks at the stage of preparing the liposomes has been solved, namely, the optimal parameters for obtaining lipid film, providing uniform of liposome size, low impurity and alcohol content. Methods and results. As a substance «Lipoid C 100» has been used. Determination of ethanol has been done by the method of gas chromatography, the determination of impurities (phosphatidylcholine and lysophosphatidylcholine) - by the method of liquid chromatography. Conclusions. According to the research it has been found that the speed of rotation of the flask, the amount of feed solution of lipoid and deoxycholic acid affect the formation of impurities and ethanol content. The atmosphere, in which the formation of lipid film is done, influences the formation of impurities and almost do not influence on the amount of ethyl alcohol. The optimal loading of raw material is 10 % of the volume of the flask. The optimum rotational speed of the flask is 50 rev/min., the number of cycles of nitrogen is 4.